“We are the minority”: Latinx student-athletes experiences within their Predominantly White Institutions - Alanis, Melody; Cunningham, George B.; Brison, Natasha T. (Journal of Intercollegiate Sport, 2024)
Despite the burgeoning Latinx student population in the United States, a conspicuous gap exists in the academic literature, particularly within the National Collegiate Athletic Association (NCAA) context. Consequently, the central objective of this study was to redress this void by analyzing the racial experiences encountered by NCAA Division I Latinx student-athletes enrolled in Predominantly White Institutions (PWIs). To fulfill this objective, the researchers applied a qualitative phenomenological approach, seeking an in-depth comprehension of the significance of diversity practices within the distinct educational milieus inhabited by the study’s participants. Employing Latin Critical Race Theory (LatCrit) as the theoretical framework, the authors gathered data through six semi-structured interviews and supplemented this information with pertinent diversity and inclusion-related information derived from each participating university and the respective athletic programs. The study’s findings underscored the persistent issue of racial discrimination confronted by NCAA Division I Latinx student-athletes within the university setting. Remarkably, despite the extensive diversity, equity, and inclusion (DEI) trainings and councils within these institutions, Latinx student-athletes continued to grapple with racial disparities. Indeed, recurring themes from the data highlighted their significant reliance on familial support and campus resources as strategies for navigating and mitigating these challenges. In light of a substantial body of scholarly work that recognizes the critical importance of DEI in sport, this study serves as a poignant reminder of the pressing need for further academic and practical endeavors aimed at effectively addressing racial disparities.